Assessment of Damage to Nucleic Acids and Repair Machinery in Salmonella typhimurium Exposed to Chlorine. (16th July 2009) - Phe, M. H.; Hajj Chehade, M.; Guilloteau, H.; Merlin, C.; Block, J. C.
Abstract : Water disinfection is usually evaluated using mandatory methods based on cell culturability. However, such methods do not consider the potential of cells to recover, which should also be kept as low as possible. In this paper, we hypothesized that a successful disinfection is achieved only when the applied chlorine leads to both intracellular nucleic acid damage and strong alterations of the DNA repair machinery. Monitoring the SOS system responsiveness with a umuC'-'lacZ reporter fusion, we found that the expression of this important cellular machinery was altered after the beginning of membrane permeabilization but prior to the total decline of both the cell culturability and the nucleic acid integrity as revealed by Sybr-II staining. Rapid measurement of such nucleic acid alterations by fluorochrome-based staining could be used as an alternative method for assessing the effectiveness of disinfection with chlorine.